Numerical Analysis of RC Slab with opening strengthened with CFRP Laminates. Issue 4 (September 2019) - Mohamed, Osama; Khattab, Rania; Okasha, Nader
Abstract: Openings in reinforced concrete (RC) structural floor slabs are sometimes necessary created as a result of variations in architectural function or structural upgrades, amongst other reasons. Architecture reasons for making openings may include change-of-usage, or improvement of air circulation, and lighting. Openings in structural slabs may reduce their strength and stiffness or may transform the original failure mode of the slab to different failure patterns. In the past decades, externally bonded fiber reinforced polymer (FRP) sheets have become popular to strengthen or rehabilitate RC structures for traditional force actions such as flexural, shear, or torsion. Strengthening and rehabilitation of beams, floor slabs, and columns may be necessary for seismic or non-seismic applications. This paper reports the results of numerical study to evaluate the effectiveness of strengthening of two-way RC floor slabs with openings, using carbon FRP (CFRP) composite sheets. Ten numerical models were created, consisting of a reference model with the slab having opening but not strengthened, and nine models with an opening and CFRP laminates applied to the tension side of the slab. The strengthening laminates varied in thickness and width. The results indicate that CFRP laminates can significantly enhance both the flexural capacity and overall stiffness of the floor slab containing openings. Increasing the thickness of CFRP laminates decreases the deflection of mid span. Load-deflection curves were generated, and ultimate load, and ductility index were discussed.